2011
DOI: 10.1016/j.cell.2011.08.038
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Repair Complex Functions as an Oct4/Sox2 Coactivator in Embryonic Stem Cells

Abstract: SUMMARY The transcriptional activators Oct4, Sox2 and Nanog cooperate with a wide array of cofactors to orchestrate an embryonic stem (ES) cell-specific gene expression program that forms the molecular basis of pluripotency. Here we report using an unbiased in vitro transcription-biochemical complementation assay to discover a multi-subunit stem cell coactivator complex (SCC) that is selectively required for the synergistic activation of the Nanog gene by Oct4 and Sox2. Purification, identification and reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
242
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(261 citation statements)
references
References 58 publications
18
242
0
Order By: Relevance
“…Furthermore, in response to DNA damage, human Rad23B was found to interact with ubiquitylated p53, localize at chromatin and accumulate at the p21 promoter 59 . In addition, in mouse embryonic stem cells, several components of the NER complex, including Rad23B, have been shown to act as an Oct4/ Sox2 co-activator complex that associates with chromatin and is required for stem cell maintenance 60 . Recruitment of NER factors to active promoters has also been reported in HeLa cells in the absence of DNA damage 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in response to DNA damage, human Rad23B was found to interact with ubiquitylated p53, localize at chromatin and accumulate at the p21 promoter 59 . In addition, in mouse embryonic stem cells, several components of the NER complex, including Rad23B, have been shown to act as an Oct4/ Sox2 co-activator complex that associates with chromatin and is required for stem cell maintenance 60 . Recruitment of NER factors to active promoters has also been reported in HeLa cells in the absence of DNA damage 61 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that no one single chromatin modification may be responsible for the inability of CS and XP/ CS cells to restart transcription, but, rather, a combination of several deficiencies may create a "perfect storm" for the subsequent heterochromatinization of these promoters. It is not surprising that XPD mutations result in a chromatin dysregulation, as more recent studies place NER factors at the intersection between transcription and repair by regulating chromatin structure (24,(29)(30)(31).…”
Section: Sirt1 Mediates Repression Of Hk Genes In Xp-d/cs Cells After Uvmentioning
confidence: 99%
“…The fact that the so-called global transcriptional arrest displayed by XP/CS and CS cells excludes genes that are activated upon DNA damage, such as p53-dependent genes, suggests that there must be an active transcriptional repression process, rather than a physical blocking of transcription. In this regard, CSB and other NER factors have been shown to affect chromatin remodeling for optimal transcription initiation (24,(29)(30)(31).…”
mentioning
confidence: 99%
“…Aiming to discern the biochemical pathways required for the efficient and safe reprogramming of adult somatic cells into iPSCs, recent studies have shown the relevance of telomere homeostasis [2][3][4], signal transducers, and DNA repair proteins [4][5][6][7] in cell reprogramming. These results have shown that a significant DNA stress-reflected by an increased number of DNA double strand breaks (DSBs)-is produced during the reprogramming process.…”
Section: Introductionmentioning
confidence: 99%